Enhancing student conceptual understanding and critical thinking through SETS-based digital modules on environmental changes - Evin Kustantia; Mieke Miarsyah; Diana Vivanti Sigit (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
The rapid advancements in science and technology have necessitated the adaptation of biology education to enhance students' understanding and critical thinking skills, aligning with the demands of the 21st century. The development of digital modules based on the Science, Environment, Technology, and Society (SETS) framework represents an innovative approach to facilitate students' learning by seamlessly integrating theories from science, environment, technology, and society. This research adopts the Research and Development methodology, employing the ADDIE development model. The digital module's development underwent validation by four experts, comprising two media experts and two material experts. The validation results yielded a 90% agreement from media experts and an 85% concurrence from material experts, indicating the suitability of the digital module on environmental change, grounded in the SETS framework, for educational use. The developed module was subjected to testing using a one-group pretest-posttest design, followed by the analysis of the obtained data through paired sample t-tests. The analysis results indicate a significant improvement in both conceptual understanding and critical thinking skills following the utilization of the module. Hence, this module is recommended for use in biology education, particularly in the context of environmental change materials.